DECISION SUPPORT SYSTEM FOR DETERMINING SCHOLARSHIP RECIPIENTS USING TOPSIS FMADM METHOD - Husein, Ismail; Juliandri, Dedy (ZERO: Jurnal Sains, Matematika dan Terapan, 2017)
Granting scholarships to students aims to assist students in conducting lectures. Distribution of scholarships conducted by Muslim University Nusantara Al-Washliyah to help underprivileged or underachievers during their study The problem aims to choose some best alternative based on some attributes (criteria) used. In order to make decisions on fuzzy issues can be used Fuzzy Multiple AttributeDecision Making (FMADM). In this research modeling using Unified Modeling Language (UML) in FMADM with TOPSIS method and Weighted Product to select candidates of scholarship recipients.